Exploring quinoxaline derivatives: An overview of a new approach to combat antimicrobial resistance - Khatoon, Hena; Mohd Faudzi, Siti Munirah (Elsevier Masson, 2024)
Antimicrobial resistance (AMR) has emerged as a long-standing global issue ever since the introduction of penicillin, the first antibiotic. Scientists are constantly working to develop innovative antibiotics that are more effective and superior. Unfortunately, the misuse of antibiotics has resulted in their declining effectiveness over the years. By 2050, it is projected that approximately 10 million lives could be lost annually due to antibiotic resistance. Gaining insight into the mechanisms behind the development and transmission of AMR in well-known bacteria including Escherichia coli, Bacillus pumilus, Enterobacter aerogenes, Salmonella typhimurium, and the gut microbiota is crucial for researchers. Environmental contamination in third world and developing countries also plays a significant role in the increase of AMR. Despite the availability of numerous recognized antibiotics to combat bacterial infections, their effectiveness is diminishing due to the growing problem of AMR. The overuse of antibiotics has led to an increase in resistance rates and negative impacts on global health. This highlights the importance of implementing strong antimicrobial stewardship and improving global monitoring, as emphasized by the World Health Organization (WHO) and other organizations. In the face of these obstacles, quinoxaline derivatives have emerged as promising candidates. They are characterized by their remarkable efficacy against a broad spectrum of harmful bacteria, including strains that are resistant to multiple drugs. These compounds are known for their strong structural stability and adaptability, making them a promising and creative solution to the AMR crisis. This review aims to assess the effectiveness of quinoxaline derivatives in treating drug-resistant infections, with the goal of making a meaningful contribution to the global fight against AMR.